Asian Englishes: Some reflections - Quayum, Mohammad Abdul (IIUM Press, 2016)
Editorial introduction to the special issue of Asiatic: IIUM Journal of English Language and Literature on contemporary Asian Englishes. Comments on the history of the English language in the Asian continent, the present state of its prevalence, its development into different varieties and the role of literature in the formation of English to an emergent/emerging Asian language,